OʻZBEKISTONDA INVESTITSIYALAR OQIMI VA IQTISODIY OʻSISH OʻRTASIDAGI BOGʻLIQLIKNI BAHOLASH (Marketing Journal, 2026)
AbstractThis article provides a scientific assessment of the relationship betweeninvestment inflows and economic growth in Uzbekistan. The relevance of the study isexplained by the need to determine the impact of increasing investment volumes on thegrowth rate of gross domestic product. The research methodology is based on statisticaldata analysis, econometric methods, regression modeling, and comparative analysis.The results reveal a positive and statistically significant relationship between investment inflows and economic growth. In particular, foreign direct investment isidentified as a key factor accelerating economic growth. The author proposes practicalrecommendations aimed at improving investment policy and enhancing the investmentclimate.Keywords: investment inflows, economic growth, gross domestic product,foreign direct investment, investment policy, statistical analysis.